Pengembangan Bahan Ajar Flipbook Digital LANDMART (Landslide Mitigation and Readiness Training) Berbasis Etno-STEM untuk siswa SMP - Rina Rianti; Sjaifuddin; Lulu Tunjung Biru (PendIPA Journal of Science Education, 2026)
This research is motivated by the limitations of disaster programs and the lack of disaster teaching materials in disaster-prone schools that lead to low student preparedness. Based on these problems, the Ethno-STEM-based LANDMART (Landslide Mitigation and Readiness Training) Digital Flipbook was developed as an alternative solution to make students have disaster preparedness, especially for junior high school students. This study aims to analyze the level of validity of the developed product and examine the level of readability of students in the Ethno-STEM-based LANDMART Digital Flipbook. This study uses the Research and Development (R&D) method adapted from the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. Validity testing was carried out using instruments given to material experts, media experts, and teaching materials experts. A limited-scale trial was conducted through a readability test on 30 students from two different schools. The data obtained were analyzed using quantitative and qualitative descriptive methods to obtain an overview of the feasibility and readability of the product. The results of the study showed that the product validation level achieved a score of 91.98%, categorized as "very valid." Specifically, validation from material experts achieved 88.93%, media experts 93.71%, and teaching materials experts 93.32%, categorized as "very valid." Furthermore, the readability test obtained an average score of 93.6%, categorized as "very good."